Identifikasi Senyawa Tanin Dan Evaluasi Ekstrak Kulit Alpukat Persea Americana Mill Sebagai Lotion - Silfi Arini Durri; Muhammad Walid (Journal Clinical Pharmacy and Pharmaceutical Science, 2024)
Avocado is a fruit that is rich in vitamin content including vitamin A, vitamin B, vitamin C and also vitamin E which can be beneficial for body health and can be used as a cosmetic to maintain skin moisture. Therefore, in this study, lotion will be made from avocado fruit extract. The purpose of this research was carried out in an experimental way. Extraction was carried out by maceration method using 96% ethanol then lotion preparation formulation test was carried out and to determine the stability of physical quality, then organoleptic test, homogeneity test, pH test, spreadability test and phytochemical screening and tannin test were carried out. The results showed that avocado skin extract contains tannin compounds using 3 different reagents, using fecl3 reagent produces a blackish green color then with gelatin reagent produces a white precipitate and the last with pb acetate reagent produces a white endapat so from these 3 reagents it can be concluded that it positively contains tannins. In the lotion dosage formulation, the evaluation results consist of organoleptical tests, the results obtained in replicates 1 to 3 have no difference in terms of shape, color, and odor, homogeneity test results obtained in replicates 1 to 3 obtained homogeneous dosage forms, ph test results obtained in replicates 1 to 3 obtained an average result of ±7.0, irritation test results obtained in respondents 1 to 5 the results are not irritating to the skin and the spreadability test results obtained in replicates 1 to 3 obtained an average result of ±7.63 from all evaluations there are still